HIV-1 Subtype A Gag Variability and Epitope Evolution - Abidi, Syed Hani; Kalish, Marcia L.; Abbas, Farhat; Rowland-Jones, Sarah; Ali, Syed (Public Library of Science, 2014)
Objective: The aim of this study was to examine the course of time-dependent evolution of HIV-1 subtype A on a global level, especially with respect to the dynamics of immunogenic HIV gag epitopes. Methods: We used a total of 1,893 HIV-1 subtype A gag sequences representing a timeline from 1985 through 2010, and 19 different countries in Africa, Europe and Asia. The phylogenetic relationship of subtype A gag and its epidemic dynamics was analysed through a Maximum Likelihood tree and Bayesian Skyline plot, genomic variability was measured in terms of GRA substitutions and Shannon entropy, and the time-dependent evolution of HIV subtype A gag epitopes was examined. Finally, to confirm observations on globally reported HIV subtype A sequences, we analysed the gag epitope data from our Kenyan, Pakistani, and Afghan cohorts, where both cohort-specific gene epitope variability and HLA restriction profiles of gag epitopes were examined. Results: The most recent common ancestor of the HIV subtype A epidemic was estimated to be 195661. A period of exponential growth began about 1980 and lasted for approximately 7 years, stabilized for 15 years, declined for 2–3 years, then stabilized again from about 2004. During the course of evolution, a gradual increase in genomic variability was observed that peaked in 2005–2010. We observed that the number of point mutations and novel epitopes in gag also peaked concurrently during 2005–2010. Conclusion: It appears that as the HIV subtype A epidemic spread globally, changing population immunogenetic pressures may have played a role in steering immune-evolution of this subtype in new directions. This trend is apparent in the genomic variability and epitope diversity of HIV-1 subtype A gag sequences.